Development of New Convenient Recipes from Local Sudanese Fruits and Vegetables - Abdel-Rahman, Nawal Abdel-Gayoum; Mohammed, Mazaher Abdel-Rahim; Mustafa, Mona Mohammed (Pakistan Journal of Nutrition, 2011)
The purpose of this study was to prepare and formulated ready to use snack meal (paste) for school children from some local Sudanese common fruits, mango (Mangifera indica); forest fruits, baobab (Adansonia digitata) and godeim (Grewia tenax); also, vegetables, pumpkin (Telfairia occidentalis). In addition, the physico-chemical properties, storage stability and sensory quality of the product was evaluated. The results showed that the fruit paste contains high level of protein (19.36%), carbohydrates (64.25%), vitamin C (575.06 mg/100 g) and energy value (365.24 kcal). The fruit paste is containing abundant amounts of potassium and magnesium, excellent quantities of iron, calcium and phosphorous, while, its poor source for sodium for school age children from 4-17 years. The product is kindly stable during storage for 12 months at ambient temperature. However, the product is acceptable for sensory attributes as compare to control sample.